THE OPINIONS OF TEACHING MEMBERS OF COLLEGE OF AGRICULTURE-TIKRIT UNIVERSITY REGARDING THE SIZE AND IMPORTANCE OF DSERTIFICATION PROBLEMS IN SALAHDDIN GOVERNARATE AND ITS RELATION WITH SOME VARIABLES - Ghaidhaib, Ali Ahmed (Diyala Agricultural Sciences Journal, 2018)
The research aims were to determine the size and the importance of desertification problems in Salahddin governorate and relationship between the size of the problems and their importance, and to determine correlation between the size and the importance of these factors with independent variables (getting study, specification, scientific position, numbers of their academic years, and numbers of the published researchers). The research include all the lectures in the college of Agriculture in Tikrit University whose amount were 91 lecturers. After omitting the random sample which amounted 30 lecturers, the questionnaire was used as a tool of collection of data, which include three parts. The first part dealing with the lecturers, the second part include tool to measure the size and the importance of desertification problem which include 21 items. The third part included question about the sudation of the treatment of densification problem, the validity and reliability was account usin spilt- half which is (0.92). The results showed that there was obvious approach in their answer between the ranking of the size of the problem, the first one for this problem was the lower funding for treatment of this problem, while significant correlation among all the studied variables and lake of professional officials was found. The research recommendations are focusing on desertification problems, desertification causes and its treatment ways.